Modern radiotherapy - Angel Montero-Luis; Ivica Ratoša; Helena Barbara Zobec Logar (Onkologija)
The evolution of modern radiotherapy aligns seamlessly with the principles of Citius, Altius, Fortius—faster, higher, stronger— while embracing the Less is More philosophy. In recent years, the 5-fraction radiotherapy regimen has emerged as a transformative approach, offering shorter treatment durations, higher precision, and enhanced therapeutic efficacy, all while optimizing healthcare resources. Evidence from large prospective trials has confirmed its efficacy in breast, prostate, lung, and rectal cancers, as well as in the management of oligometastatic disease. Furthermore, technological advancements in imaging, stereotactic techniques, and dose delivery have played a crucial role in ensuring the safety and precision of these treatments. Beyond clinical efficacy, the benefits of 5-fraction radiotherapy extend to improving patient quality of life, reducing treatment burden, and enhancing healthcare efficiency. In the era of modern radiotherapy, Citius, Altius, Fortius prevails—because Less is More, and the future is now.